Questioning the Question: How can a husband rape his wife? A Discussion in an International Classroom (Journal of Comparative Social Work, 2014)
This essay discusses the question “How can a husband rape his wife?” I assume that upon reading this you already have some reaction or answer. I have one, too. The interesting part is that they can be very different. Some people think along the lines of “Yes, I can't imagine how a husband can rape his wife because that is so cruel.” Other people may think something like “Yes, how is this even possible, that a husband having sex with his wife could be considered rape.” These views are quite different, and it is this difference that interests me.In this essay, I will reflect upon the question “How can a husband rape his wife?” I will discuss my personal background, and describe the situation and experience in which this question was brought up. Next, I will discuss various reflections I have had about this difference. I will then reflect on how this idea, or even the definitions of the terms, may be based on a person’s culture, gender, and/or opinions. After that, I will look at how this topic may affect social workers, service users and social work as a profession. Lastly, I will also explain how this has helped me gain a better understanding of this issue.